Issues of Cyber security and its solutions in Nepalese Context - Gupta, Lokesh (NPRC Journal of Multidisciplinary Research, 2024)
In today's digital age, the internet's expansion has brought great convenience but also raised cyber threats. So, identify the issue of cyber-security and its solution in Nepalese context is significant. Descriptive design and qualitative methods were employed, with data sourced from Google Scholar and analyzed through thematic analysis. The study shows a myriad of issues stemming from inadequate cyber security awareness in Nepal, including increased vulnerability to cyber-attacks, data breaches, and societal, economic, and regulatory consequences. Bridging the gap in cyber security awareness is imperative to mitigate risks effectively and foster a secure digital environment in Nepal. Strategies emphasizing education, training, and regulatory frameworks are vital for addressing these challenges and promoting technological advancement and societal trust. This study proposes AI-driven solutions to address the lack of cyber security awareness in the Nepalese context, offering a unique approach to mitigate cyber threats and foster a secure digital environment.